2012
DOI: 10.2219/rtriqr.53.141
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Forecast Train Information and Consequential Impact on Decision Making for Train-choice

Abstract: Keywords: train information provision, train choice, passengers' behavioral mode, travel delaytrains, their reasons for choosing them, the level of difficulty in choosing trains, and also passenger reactions to being given information about arrival sequences, which turned out to be incorrect. Providing detailed information about individual trains Attitude to train traffic information in the case of disruptionsPrevious research [1, 2] has already examined and highlighted the specific types of information that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…SP survey studies include [31], who studied the modal shift behavior of rail users after incidents. Fukasawa et al [32] investigated the effect of providing information such as estimated arrival time, arrival order, and congestion level on passengers' modal shift behavior in response to an unplanned transit disruption. Similar research was conducted by [33], who found that various socioeconomic attributes and experience with the systems had strong influences on travelers' behavioral responses in the context of real-time information.…”
Section: ) Individual Behaviormentioning
confidence: 99%
“…SP survey studies include [31], who studied the modal shift behavior of rail users after incidents. Fukasawa et al [32] investigated the effect of providing information such as estimated arrival time, arrival order, and congestion level on passengers' modal shift behavior in response to an unplanned transit disruption. Similar research was conducted by [33], who found that various socioeconomic attributes and experience with the systems had strong influences on travelers' behavioral responses in the context of real-time information.…”
Section: ) Individual Behaviormentioning
confidence: 99%
“…SP survey studies include Kamaruddin et al (2012), who studied the modal shift behavior of rail users after incidents. Fukasawa et al (2012) investigated the effect of providing information such as estimated arrival time, arrival order, and congestion level on passengers' modal shift behavior in response to an unplanned transit disruption. A similar research was conducted by Bai and Kattan (2014), who found that various socioeconomic attributes and experience with the systems had strong influences on travelers' behavioral responses in the context of real-time information.…”
Section: Individual Behaviormentioning
confidence: 99%
“…Similarly, Fukasawa et al investigated the effect of providing information such as estimated arrival time, arrival order, and congestion level on passengers’ modal shift behavior in response to unplanned transit disruption using a data from an SP survey ( 20 ). They found that train users who have access to the information generally have a higher tendency of shifting to other trains in comparison with those without access to the information.…”
Section: Literature Reviewmentioning
confidence: 99%